Análisis psicológico del mensaje de las sirenas en la Odisea de Homero - Aracena, Moisés (Revista Chilena de Humanidades, 2015)
Professor Aracen¡1's contribution points to the use fulne ss of psyc hologicalstudies in the field ofliterary creation . Here he re fers to the artistic expression of psychological needs which, as in the case of the Homeric episode of the sirens' songs, acquire an aesthetic as well as an ethical dimension, where the wise message is interpreted with considerable empathy, although it might well bedoubted that such needs would necessa rily represent prope rl y virtuous needs towhich man should aspire.